Selenium deficiency fastens intestinal barrier dysfunction and inflammation during high-fat/high-fructose-induced MASLD development in male mice - Nora Meinhardt; Anja R. Geisler; Laura Otto; Yvonne Hupfer; Betty Hebecker; Bill J. Perkowski; Markus Werner; Kristina Lossow; Marcus Ebert; Sandra Burghoff; Oliver Werz; Stefan Lorkowski; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Combined Effects of Nitrogen Deposition and Climate on Root-to-Shoot Ratios and Root Morphology in Temperate Tree Regeneration - Viktoria Dietrich; Jörg Niederberger; Nico Espadilha Patriarca; Meike E. Becker; Stefan Müller; Hannah Lorösch; Sophie Boll; Naima Hoque; Helena Jüngling; Nico Beck; Adrian Dierks; Pauline Ebert; et al. (Ecosystems, 2025)
Nitrogen (N) availability is known to interact with the drought tolerance in plants, but its effects on the morphological acclimation of forest trees to low precipitation have rarely been investigated. Based on a Germany-wide field-study design covering different combinations of climatic conditions and atmospheric N deposition, we harvested young trees up to 70 cm in height of Fagus sylvatica , Quercus petraea , Pseudotsuga menziesii , and Abies alba . We tested the hypothesis that high N deposition decreases the root/shoot ratio, alters fine root morphology (for example, by reducing specific root length of absorptive roots) and reduces mycorrhizal colonization rate, which are factors that would reduce the capacity for water uptake under drought. European beech showed reduced root/shoot ratios at high N deposition and reduced specific root length and mycorrhizal colonization of absorptive roots at sites with both high N deposition and low precipitation. These observations were consistent with the optimal portioning theory, as less investment in belowground biomass was required to meet the N demand at high N deposition. Sessile oak showed no effect of N deposition or mean annual precipitation on the parameters studied, indicating that the gradients studied were not large enough to cause changes. Douglas-fir and silver fir expanded their root systems with increasing N deposition, with higher specific root length in Douglas-fir and a trend towards higher root tip abundance in silver fir. Thus, in contrast to European beech, we found no indication that the tree's ability to cope with drought was reduced by high N deposition in sessile oak, Douglas-fir, and silver fir. The combined negative effect of drought and high N deposition on the root system in European beech as Central Europe’s most dominant tree species in the natural vegetation emphasizes the need for curtailing N emissions, especially from agriculture.

Geostatistischer Datensatz zur Temperaturauswirkung (0–80 °C) auf die Hydrochemie pleistozäner Grundwasserleiter – Labor- und Feldexperimente für gelöste Hauptkomponenten - Klas Lüders; Götz Hornbruch; Ralf Köber; Markus Ebert; Andreas Dahmke (Grundwasser, 2025)
Zusammenfassung Das Klimaschutzpotenzial einer verstärkten thermischen Nutzung des oberflächennahen Untergrundes als saisonaler Speicher bleibt bisher weitestgehend ungenutzt. Als Hindernis wird häufig die Besorgnis vor negativen Veränderungen der Grundwasserchemie angeführt, welche für den Hochtemperatur-Bereich (HT-Bereich) (≤ 90 °C) jedoch größtenteils auf relativ einfachen Laboruntersuchungen beruht. Mit der Zusammenstellung (un)publizierter Labor- und Felddaten für C org -arme, teilentkalkte pleistozäne bzw. jungtertiäre Lockersedimente wird dieser Diskussion hier eine erste empirische Datengrundlage gegeben. Darin zeigen Konzentrationsspannbreiten der gelösten Hauptkomponenten bei natürlichen (10 °C) und erhöhten (25, 40, 70 °C) Temperaturen, außer bei K, Si und OC, jeweils eine größere natürliche Variabilität als temperaturinduzierte Änderungen. Wie auf Basis begleitender Batchversuche erwartbar, überschritten Si gel. und DOC in einem zyklischen HT-Aquifer-Wärmespeicher-Feldversuch (≤ 80 °C) die Konzentrationsspannbreiten des Baseline-Monitorings. Die hydrochemisch modifizierte Abstromfahne blieb jedoch während des gesamten (Post)Betriebs-Monitorings auf < 30 m Entfernung zum ‚warmen‘ Brunnen begrenzt. Mit Blick auf die Grundwasserqualität muss diese empirische Datengrundlage zukünftig auf Spurenkomponenten und weitere Aquifertypen wie bspw. C org -reichere Sedimente erweitert werden.

Significance of temperature as a key driver in ZVI PRB applications for PCE degradation - Adrian D. Metzgen; Andreas Dahmke; Markus Ebert (Journal of Contaminant Hydrology, 2023)

Improved correction formulas to estimate iohexol clearance from simple models - Qian Dong; Uwe Fuhr; Elke Schaeffner; Markus van der Giet; Natalie Ebert; Max Taubert (European Journal of Clinical Pharmacology, 2023)

Correction to: Human skin-derived ABCB5+ stem cell injection improves liver disease parameters in Mdr2KO mice - Vanessa Hartwig; Bedair Dewidar; Tao Lin; Anne Dropmann; Christoph Ganss; Mark Andreas Kluth; Nils Tappenbeck; Lysann Tietze; Bruno Christ; Markus Hermann Frank; Roger Vogelmann; Matthias Philip Alexander Ebert; et al. (Archives of Toxicology, 2019)

Human skin-derived ABCB5+ stem cell injection improves liver disease parameters in Mdr2KO mice - Vanessa Hartwig; Bedair Dewidar; Tao Lin; Anne Dropmann; Christoph Ganss; Mark Andreas Kluth; Nils Tappenbeck; Lysann Tietze; Bruno Christ; Markus Frank; Roger Vogelmann; Matthias Philip Alexander Ebert; et al. (Archives of Toxicology, 2019)

Induction of Early Growth Response-1 Mediates Microglia Activation In Vitro But is Dispensable In Vivo - Thomas Langmann; Stefanie Ebert; Yana Walczak; Karin Weigelt; Markus U. Ehrengruber; Thorsten Stiewe; Bernhard H. F. Weber (NeuroMolecular Medicine, 2009)

pH-Wertpufferung im Abstrom von Reaktionswänden - Volkmar Plagentz; Dirk Schäfer; Ralf Köber; Markus Ebert; Andreas Dahmke; Frank Dethlefsen (Grundwasser, 2006)

CKW-Abbaupotenzial im Abstrom von Fe0-Reaktionswänden - Volkmar Plagentz; Markus Ebert; Andreas Dahmke (Grundwasser, 2005)

Prognostizierte und tatschliche Langzeitstabilitt von Fe(0)-Reaktionswnden?Am Beispiel der Reaktionswand am Standort Rheine nach 5-jhriger Betriebszeit - Anika Parbs; Markus Ebert; Martin Wegner; Volkmar Plagentz; Dirk Schfer; Ralf Kber; Andreas Dahmke (Grundwasser, 2003)

Einsatz reaktiver Tracer zur Bewertung der Langzeitstabilitt und Reaktivitt von Fe(0)-Reaktionswnden - Anika Parbs; Markus Ebert; Ralf Kber; Volkmar Plagentz; Hermann Schad; Andreas Dahmke (Grundwasser, 2003)